2021
DOI: 10.1007/s15010-021-01642-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microbiological diagnosis on the clinical course of spondylodiscitis

Abstract: Purpose This study sought to recognize differences in clinical disease manifestations of spondylodiscitis depending on the causative bacterial species. Methods We performed an evaluation of all spondylodiscitis cases in our clinic from 2013–2018. 211 patients were included, in whom a causative bacterial pathogen was identified in 80.6% (170/211). We collected the following data; disease complications, comorbidities, laboratory parameters, abscess occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
5
18
2
1
Order By: Relevance
“…Furthermore, another study found that 60% of all cases with S. aureus detection had (or progressed to developing) an epidural, paraspinous or psoas abscess [36]. Although in our study the 2.3 increased odds were just barely not statistically significant, combined with recent literature we believe an additional risk-point should be awarded indicating higher risk of a fast, more aggressive disease progression or failure of therapy [37].…”
Section: Discussioncontrasting
confidence: 49%
“…Furthermore, another study found that 60% of all cases with S. aureus detection had (or progressed to developing) an epidural, paraspinous or psoas abscess [36]. Although in our study the 2.3 increased odds were just barely not statistically significant, combined with recent literature we believe an additional risk-point should be awarded indicating higher risk of a fast, more aggressive disease progression or failure of therapy [37].…”
Section: Discussioncontrasting
confidence: 49%
“…Spondylodiscitis is an infection of the vertebral body and/or the intervertebral disc space. and is mainly caused by Staphylococcus aureus and Escherichia coli [ 73 ]; while infections with C. acnes are rare, they occur. In 2010, Uckay et al reported 29 patients with spondylodiscitis caused by C. acnes who presented with back pain [ 74 ].…”
Section: Evidence For C Acnes Biofilms In Vivomentioning
confidence: 99%
“…Similar prevalence was observed by Stangenberg in 211 patients. 31 Pola et al 29 found that 53 patients had multifocal involvement (26%). Of note, the prevalence of comorbidities in this study was almost 70%.…”
Section: Discussionmentioning
confidence: 99%